Pengungkapan Marah di Jejaring Sosial - Safinatunnajah Safinatunnajah; Ilmi Amalia (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
The aim of this study was to determine the effect of the big five personality, social support, collectivism-individualism, and anonymity on expressing anger on social networking sites (SNS). This research used quantitative with multiple regression analysis methods. The samples in this study were 210 respondents who posted anger content on social networking sites, aged at least more than 18 years old. Obtained by non-probability sampling technique. In this study, researcher adapted and collected the data with four questionnaires; the anger-out scale is from STAXI measuring instrument, Big Five Inventory (BFI), Interpersonal Support Evaluation List, and collectivism-individualism. To test the validity of the instrument, researcher was using Confirmatory Factor Analysis (CFA). The results showed there was a significant difference from the type of big five, social, collectivism-individualism and anonymity to expressing anger on social networking sites by 18.6.